An Image Coding and Embedding Strategy Based on Channel Variations and DNA Sequences - Abdulminuim, Matheel Emaduldeen (Iraqi Journal of Science, 2022)
The digital multimedia systems become standard at this time because of their extremely sensory activity effects and also the advanced development in its corresponding technology. Recently, biological techniques applied to several varieties of applications such as authentication protocols, organic chemistry, and cryptography. Deoxyribonucleic Acid (DNA) is a tool to hide the key information in multimedia platforms.In this paper, an embedding algorithm is introduced; first, the image is divided into equally sized blocks, these blocks checked for a small amount color in all the separated blocks. The selected blocks are used to localize the necessary image information. In the second stage, a comparison is between the initial image pixel and the watermark bit pixel is done to select the key that represents the location of a specific bit location that exist in all channels with its most dominant. If the compared bits are equal then (0) is added in least significant bit of least dominant color channel otherwise (1) is added. In the last stage, a regeneration process for the key is done. DNA based cryptographic algorithm has been suggested to develop secures image encryption techniques. This algorithm gives a good results, the MSE was (0.0007) for one test also the key generation method is successful.